Pengaruh Kualitas Pelayanan Kepuasan Nasabah dan Citra Perusahaan terhadap Loyalitas Nasabah BMT UGT Sidogiri Cabang Glenmore Kabupaten Banyuwangi - Anang Asari (MOMENTUM : Jurnal Sosial dan Keagamaan, 2022)
The present study aims to determine how the service quality, customer satisfaction, and corporate image can impact on customer’s loyalty at BMT UGT Sidogiri Glenmore Branch. After exploring the literature review, this study determines that essential variables have strongly suspected of influencing customer’s loyalty, namely service quality, customer satisfaction, and company image. The variables identified is a basic strategy for developing customer loyalty. This research employs quantitative explanatory research to analyze service quality, customer satisfaction, and company image on customer loyalty using a survey method. While probability sampling with accidental sampling method was used to determine the sample, the sample size of the sample was determined using Ferdinand's theory. As a result, 325 respondents were collected. Multiple linear regression analysis tools, with the help of SPSS version 22 were used to analyze the data. The analysis results show that the service quality variable has a significant effect on customer loyalty with Sig. 0.037. Customer satisfaction has a significant impact on customer loyalty with Sig. 0,000. Company image has a substantial impact on customer loyalty with Sig. 0,000. These variables (simultaneously) have significantly impacted on customer loyalty with a value of F count 71.390 ≥ F table 3.20 and a significance of 0.000 ≤ 0.05. Then, the R2 test used (coefficient of determination) was 0.220 or 22%. However, the researcher did not examine further the other variables influence the remaining 78% in this study.